A protein engineered to bind uranyl selectively and with femtomolar affinity - Zhou, Lu; Bosscher, Mike; Zhang, Changsheng; Özçubukçu, Salih; Zhang, Liang; Zhang, Wen; Li, Charles J.; Liu, Jianzhao; Jensen, Mark P.; Lai, Luhua; He, Chuan (Nature chemistry, 2014)
Uranyl (UO 2 2+ ), the predominant aerobic form of uranium, is present in the ocean at a concentration of ~3.2 parts per 10 9 (13.7 nM); however, the successful enrichment of uranyl from this vast resource has been limited by the high concentrations of metal ions of similar size and charge, which makes it difficult to design a binding motif that is selective for uranyl. Here we report the design and rational development of a uranyl-binding protein using a computational screening process in the initial search for potential uranyl-binding sites. The engineered protein is thermally stable and offers very high affinity and selectivity for uranyl with a K d of 7.4 femtomolar (fM) and >10,000-fold selectivity over other metal ions. We also demonstrated that the uranyl-binding protein can repeatedly sequester 30–60% of the uranyl in synthetic sea water. The chemical strategy employed here may be applied to engineer other selective metal-binding proteins for biotechnology and remediation applications. The extraction of uranium from seawater is limited by the high concentrations of carbonate and competing metal ions. Now, a highly selective uranyl-binding protein with femtomolar affinity has been developed. This protein can extract up to 60% uranium from synthetic seawater when immobilized on bacterial cell surfaces or amylose resin.